Synthesis of aligned carbon nanotubes from waste chicken fat using thermal chemical vapour deposition method for field emission devices - Nor Dalila Abd Rahman (Tanjong Malim, 2016)
Synthesis of aligned carbon nanotubes from waste chicken fat using thermal chemical vapour deposition method for field emission devices by Nor Dalila Abd Rahman